Strengthening the community against the impacts of flooding & earthquakes through a mixed-use disaster resilience hub in Pasig City - Manzo, Kara Therese R.; Santos, Frederick C. (Quezon City College of Architecture, University of the Philippines Diliman, 2023)
Pasig City is already susceptible to damage from floods and earthquakes due to its geographical context, but the urbanization trend over the past few years has further increased that risk. The growth in population and increase in built developments has resulted in environmental degradation, lessening the protective ecosystems that naturally mitigate the risks of disasters. While the local government has made strides towards improving their disaster risk reduction and management program, there continues to be a shortage of spaces for disaster preparedness and disaster response, resulting in a growing disconnect between the city and its inhabitants: they are unprepared and unequipped to deal with the negative impacts of such disasters. Despite being one of the busiest areas in the city, the Ortigas Center lacks the appropriate facilities—fire stations, relief distribution centers, evacuation centers— which are critical in helping the community recuperate as they provide the needed response and recovery efforts to those affected.
This project addresses the growing need for safe spaces within the city to mitigate the impacts of disasters on the community. In line with the city’s land use agenda for urban development, this project proposes a development that utilizes the site’s strategic location by functioning as a mixed-use disaster resilience center and social hub that is accessible not only by those in the immediate vicinity, but even those in nearby affected cities. By equipping them with the needed skills and providing the necessary life-saving resources when such disasters occur, their susceptibility to damage from disasters may be lessened. By supplementing the city’s disaster response measures while retaining the current site’s commercial land use designation, the project aims to increase the vulnerable community’s resilience to the disasters that inevitably afflict the area.
include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Emergency management -- Pasig City; Urban development -- Pasig City